Impact of a pharmacy practice research capacity‐building programme on improving the research abilities of pharmacists at two specialised tertiary care hospitals in Qatar: a preliminary study. Issue 3 (17th June 2015) - Awaisu, Ahmed; Kheir, Nadir; Alrowashdeh, Hanen Ali; Allouch, Soumaya Najib; Jebara, Tesnime; Zaidan, Manal; Mohamed Ibrahim, Mohamed Izham
Abstract Objectives The aim of this study was to develop and implement a pharmacy practice research training programme and to determine the effect of the programme on pharmacists' knowledge of, and attitudes towards, research. Methods An intensive 26‐h training programme on pharmacy practice research methodology and biostatistics was designed and delivered. Thirty pharmacists from the National Center for Cancer Care and Research and the Heart Hospital in Qatar were recruited. A pre‐test–post‐test study design was used to subjectively and objectively assess research competencies and attitudes among the trainees. Both descriptive and inferential analyses including Wilcoxon signed‐rank, McNemar χ2 and paired t‐tests were performed to assess the utility of the training (P < 0.05 was considered statistically significant). Key findings After completing the training sessions, all subjectively assessed research‐related skills were significantly improved (P < 0.05). This was also confirmed with an overall significant improvement in the objectively assessed research‐related knowledge (P < 0.05). Overall, there was a significant improvement in the mean total knowledge score after the training programme (13.4 ± 6.4 versus 20 ± 6.0; P < 0.001). A modest change was observed when attitude towards research was assessed immediately after the training. Conclusions This study demonstrated that it was feasible to design and implement a pharmacy‐tailored research training programme and that such programme could improve pharmacists' knowledge and attitude on short term. This pilot study calls for further research to investigate the long‐term outcomes of such programmes.